Declining usage of rhBMP-2 in lumbar fusions for adult spinal deformity since 2008. (January 2018) - Poorman, Gregory; Sure, Akhila; Jalai, Cyrus M.; Vira, Shaleen; Horn, Samantha R.; Diebo, Bassel; Bess, Shay; Lafage, Virginie; Passias, Peter
Highlights: FDA issued a warning in 2008 about increased risks with BMP use in cervical spine. However, BMP use subsequently decreased in lumbar spine procedures as well. Higher complication rates in BMP patients may be due to pre-existing comorbidities.